Microbacterium sp. MRS-1, a potential bacterium for cobalt reduction and synthesis of less/non-toxic cobalt oxide nanoparticles (Co3O4) - Sundararaju, Sathyavathi; Arumugam, Manjula; Bhuyar, Prakash (Elsevier, 2020)
Background: Detoxification of heavy metal pollutants in wastewater has become a serious problem to surrounding environment. This research was conducted to utilize a potential heavy metal-resistant bacterium for the remediation of cobalt metal and simultaneous synthesis of cobalt oxide nanoparticles in the form of powder for various industrial applications. Metal oxide nanoparticles have great applications in electrochemical devices such as supercapacitors, biosensors, and batteries. Method: A heavy metal-resistant bacterium Microbacterium sp. MRS-1 isolated from electroplating industrial effluent reduced cobalt ions from an initial concentration of 200 mg/L to 26 mg/L were analyzed by atomic absorption spectroscopy. Instrumental analysis of bacterially synthesized Co3O4 has been characterized. Cytotoxicity of synthesized nanoparticles was assessed by MTT assay. Results: Microbacterium sp. MRS-1 isolated from electroplating industrial effluent was found to be suitable for cobalt oxide nanoparticles as it showed tolerance towards high concentration of metal. The nutrient broth containing metal solution and Microbacterium sp. MRS-1 showed color change from light pink to dark pink indicated the formation of extracellular nanoparticles. It also converted soluble cobalt salts into less soluble cobalt oxide nanoparticles outside the cell which allows easy recovery of nanoparticles without the destruction of cells and simultaneous detoxification of toxic metal ions. Electron microscopic imaging verified that nanoparticles were predominantly surrounding the bacterial cells and SEM imaging revealed that the produced particles were in the range of 10–100 nm in size. XRD spectrum exhibited 2θ values were corresponding to cubic face-centered cobalt oxide (Co3O4) nanoparticles. Conclusion: The present study investigated new prospective for eco-friendly detoxification of toxic heavy metal Co from metal-polluted sites and the production of cobalt oxide nanoparticles in powder form for clinical and other industrial applications.